Restorative Justice as an Alternative to Law Enforcement Against the Child of Motorcycle Theft Perpetrators - Anggi, Jessyca Octavia; Berutu, Sigar P; Ardini, Aida (TATOHI: Jurnal Ilmu Hukum, 2026)
Introduction: Law enforcement is a concrete effort to reflect the moral values contained in legal norms. The increasing prevalence of motor vehicle theft committed by children is rising in Medan City, supported by complex social, economic, and psychological factors.Purposes of the Research: This research aims to analyze how law enforcement is applied to children who commit motorcycle theft in Medan City, and to identify the causative factors of children's involvement in such criminal acts.Methods of the Research: The research uses a normative juridical approach with qualitative methods through interviews, observations, and literature studies.Findings of the Research: The results indicate that law enforcement against juvenile perpetrators of motor vehicle theft in Medan City is implemented based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, prioritizing a restorative justice approach through diversion mechanisms. This approach is applied because children have not yet achieved full psychological and emotional maturity, making rehabilitation-oriented handling more appropriate. Causative factors include: weak family supervision, peer pressure, economic hardship, low moral education, emotional instability, and inadequate community security systems. Restorative justice serves as an alternative law enforcement approach that emphasizes not only legal certainty but also more humane justice for all parties.